Zirconium phytate-based proton conductors for high-temperature fuel cell applications - Nimir, Wessam Ahmed Mohamed (2023)
A Master of Science thesis in Chemical Engineering by Wessam Ahmed Mohamed Nimir entitled, “Zirconium phytate-based proton conductors for high-temperature fuel cell applications”, submitted in April 2023. Thesis advisor is Dr. Amani Al-Othman and thesis co-advisor is Dr. Muhammad Tawalbeh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).